2014
DOI: 10.1371/journal.ppat.1004419
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani Infection Causes Distinct Epigenetic DNA Methylation Changes in Host Macrophages

Abstract: Infection of macrophages by the intracellular protozoan Leishmania leads to down-regulation of a number of macrophage innate host defense mechanisms, thereby allowing parasite survival and replication. The underlying molecular mechanisms involved remain largely unknown. In this study, we assessed epigenetic changes in macrophage DNA methylation in response to infection with L. donovani as a possible mechanism for Leishmania driven deactivation of host defense. We quantified and detected genome-wide changes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 43 publications
5
103
0
1
Order By: Relevance
“…CpG densities define the chromatin accessibility of the promoters of genes encoding inflammatory cytokines and determine their transcriptional kinetics during pathogen infection 35 , and DNA methylation is stable in peritoneal macrophages during pathogen infection 36 . However, we demonstrated that Dnmt3a-mediated DNA methylation was able to prepare macrophages for rapid and strong activation after viral infection through the regulation of transcription in resident macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…CpG densities define the chromatin accessibility of the promoters of genes encoding inflammatory cytokines and determine their transcriptional kinetics during pathogen infection 35 , and DNA methylation is stable in peritoneal macrophages during pathogen infection 36 . However, we demonstrated that Dnmt3a-mediated DNA methylation was able to prepare macrophages for rapid and strong activation after viral infection through the regulation of transcription in resident macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…However, such changes can provide a window to discover novel signaling pathways implicated in host immune responses, and to understand transcriptomic regulatory responses under specific pathophysiological conditions. In this regard, recent studies reported that changes in DNA methylation patterns can rapidly occur in response to certain environmental stimuli (5456), and Pacis et al. suggested that changes in DNA methylation could contribute to short-term memory in innate immune cells, such as dendritic cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation has been particularly understudied, as a consequence of the belief that methylation marks are highly stable and unlikely to respond to environmental perturbations on a short time scale (Bierne et al 2012;Monticelli and Natoli 2013). Recent work, however, suggests that DNA methylation patterns can rapidly change in response to certain environmental cues (Klug et al 2010;Guo et al 2011;Dowen et al 2012;Marr et al 2014), raising the possibility that rapid changes in DNA methylation might play a role in innate immune responses. To date, no studies have comprehensively investigated the contribution of rapid, active changes in methylation (in contrast to passive changes during cell replication) to the regulatory programs induced by innate immune cells in response to an infectious agent.…”
mentioning
confidence: 99%
“…To date, no studies have comprehensively investigated the contribution of rapid, active changes in methylation (in contrast to passive changes during cell replication) to the regulatory programs induced by innate immune cells in response to an infectious agent. More broadly, the few studies in mammalian cells that demonstrate cell division-independent changes in DNA methylation have only focused on a small number of CpG sites and, surprisingly, have suggested that such changes are poorly predictive of changes in gene expression levels (Bruniquel and Schwartz 2003;Klug et al 2010;Guo et al 2011;Marr et al 2014). Here, we report the first comprehensive epigenome and transcriptome analysis of monocyte-derived DCsprofessional antigen-presenting cells that play a central role in bridging innate and adaptive immunity-before and after in vitro infection with live pathogenic bacteria.…”
mentioning
confidence: 99%